Environmental toxicants perturb human Sertoli cell adhesive function via changes in F-actin organization mediated by actin regulatory proteins - Xiao, Xiang; Mruk, Dolores D; Tang, Elizabeth I; Wong, Chris K C; Lee, Will M; John, Constance M; Turek, Paul J; Silvestrini, Bruno; Cheng, C Yan (Human reproduction (Oxford), 2014)
Can human Sertoli cells cultured in vitro and that have formed an epithelium be used as a model to monitor toxicant-induced junction disruption and to better understand the mechanism(s) by which toxicants disrupt cell adhesion at the Sertoli cell blood-testis barrier (BTB)? Our findings illustrate that human Sertoli cells cultured in vitro serve as a reliable system to monitor the impact of environmental toxicants on the BTB function. Suspicions of a declining trend in semen quality and a concomitant increase in exposures to environmental toxicants over the past decades reveal the need of an in vitro system that efficiently and reliably monitors the impact of toxicants on male reproductive function. Furthermore, studies in rodents have confirmed that environmental toxicants impede Sertoli cell BTB function in vitro and in vivo. We examined the effects of two environmental toxicants: cadmium chloride (0.5-20 µM) and bisphenol A (0.4-200 µM) on human Sertoli cell function. Cultured Sertoli cells from three men were used in this study, which spanned an 18-month period. Human Sertoli cells from three subjects were cultured in F12/DMEM containing 5% fetal bovine serum. Changes in protein expression were monitored by immunoblotting using specific antibodies. Immunofluorescence analyses were used to assess changes in the distribution of adhesion proteins, F-actin and actin regulatory proteins following exposure to two toxicants: cadmium chloride and bisphenol A (BPA). Human Sertoli cells were sensitive to cadmium and BPA toxicity. Changes in the localization of cell adhesion proteins were mediated by an alteration of the actin-based cytoskeleton. This alteration of F-actin network in Sertoli cells as manifested by truncation and depolymerization of actin microfilaments at the Sertoli cell BTB was caused by mislocalization of actin filament barbed end capping and bundling protein Eps8, and branched actin polymerization protein Arp3. Besides impeding actin dynamics, endocytic vesicle-mediated trafficking and the proper localization of actin regulatory proteins c-Src and annexin II in Sertoli cells were also affected. Results of statistical analysis demonstrate that these findings were not obtained by chance. (i) This study was done in vitro and might not extrapolate to the in vivo state, (ii) conclusions are based on the use of Sertoli cell samples from three men and (iii) it is uncertain if the concentrations of toxicants used in the experiments are reached in vivo. Human Sertoli cells cultured in vitro provide a robust model to monitor environmental toxicant-mediated disruption of Sertoli cell BTB function and to study the mechanism(s) of toxicant-induced testicular dysfunction.